2014
DOI: 10.1111/iju.12506
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy in the treatment of erectile dysfunction: A prospective, randomized, double‐blinded, placebo controlled study

Abstract: Abbreviations & AcronymsED = erectile dysfunction EHS = ErectionObjectives: To investigate the role of low-intensity extracorporeal shockwave therapy in the treatment of erectile dysfunction. Methods: This was a double-blinded, single-center, prospective, randomized, placebocontrolled trial. After a 2-week phosphodiesterase type 5 inhibitor washout period, patients were assessed with Sexual Health Inventory for Men, International Index of Erectile Function-ED domain scores and Erection Hardness Score. Randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 11 publications
7
103
0
3
Order By: Relevance
“…However, data on the therapeutic benefits of these treatments to restore erectile function are still scarce. Pioneer clinical studies reporting the use of low-intensity extracorporeal shock wave therapy (Li-ESWT) have shown that Li-ESWT could improve erectile function and penile hemodynamics in men with ED who respond to pharmacotherapy and convert PDE5-I non-responders to responders (1)(2)(3)(4). More clinical studies have been conducted since then revealing encouraging results, such as the improvement of International Index of Erectile Function score and/or Erectile Hardness Score and an effect that lasts up to 1 year (5-10).…”
mentioning
confidence: 99%
“…However, data on the therapeutic benefits of these treatments to restore erectile function are still scarce. Pioneer clinical studies reporting the use of low-intensity extracorporeal shock wave therapy (Li-ESWT) have shown that Li-ESWT could improve erectile function and penile hemodynamics in men with ED who respond to pharmacotherapy and convert PDE5-I non-responders to responders (1)(2)(3)(4). More clinical studies have been conducted since then revealing encouraging results, such as the improvement of International Index of Erectile Function score and/or Erectile Hardness Score and an effect that lasts up to 1 year (5-10).…”
mentioning
confidence: 99%
“…Yee et al (22) reported that there was no significant difference in IIEF and EHS scores between treatment and sham groups 13 weeks after LI-ESWT.…”
Section: Discussionmentioning
confidence: 98%
“…The reason for this may be the application of this treatment without separating ED patients into specific groups and application of different shockwaves for different durations with different protocols during the treatment. Moreover, in different studies, whether or not PDE5i was used before and during treatment may also have resulted in differences (7,17,18,19,20,21,22). Therefore, we tried to specify ED patients in our study and patients in severe ED group found to have arterial insufficiency based on penile Doppler ultrasonography results were included in the study group.…”
Section: Discussionmentioning
confidence: 99%
“…Three out of the four studies showed positive efect of ESWT on EHS scale compared to sham group. Only one study reported negative efect of ESWT on both EHS scale and IIEF score [30]. Hence, the efect of ESWT on ED is still inconclusive, although according to EHS scale, it is proven to have some potential in the treatment of ED [16].…”
Section: Eswt In the Treatment Of Erectile Dysfunction (Ed)mentioning
confidence: 99%